Diseño documental de un sistema de gestión de seguridad y salud en el trabajo para la empresa QAP INDUSTRY SAS - Hernández Barrera, María Paula (Universidad Antonio Nariño, 2022)
Cazaoferta is a “Llanera” company, founded in 2020, an e-commerce company, specialized in selling online products at web page; with several categories, offers very good prices, and electronic payment, and payment upon delivery benefits of. It was carried out a study of online shopping habits, a situational diagnosis of the company through the application of diagnostic matrices, and an e-marketing plan wasgenerated. It was found that Cazaoferta.co is in the right sector, with great growth, in the right segments, not very well positioned, lacking to expand categories and products, but it needs to implement strategies that allow to take advantage of market opportunities. The market study showed that there is good penetration in the online market; The buyers are mostly not very frequent but have a with high access to technologies and payment tools. The proposed strategies were based on improving thepositioning of the causaoferta.co brand, market penetration, expanding product categories, strengthening logistics and technology, to be applied in the company to increase growth possibilities.